Therapeutic Efficacy of Fenugreek Extract or/and Choline with Docosahexaenoic Acid in Attenuating Learning and Memory Deficits in Ovariectomized Rats - Anjaneyulu K (Journal of Krishna Institute of Medical Sciences University, 2018)
Background: Studies have demonstrated that estradiol influences cognitive functions. Phytoestrogens and many other estrogen-like compounds in plants have beneficial effects on cognitive performance in postmenopausal women. However, there is no evident report of fenugreek and choline-Docosahexaenoic Acid (DHA) on cognition in ovariectomized rats. Aim and Objectives: The present study was aimed to evaluate the therapeutic efficacy of fenugreek extract or/and choline- DHA in attenuating ovariectomy-induced memory impairment, brain antioxidant status and hippocampal neural cell deficits in the rat model. Material and Methods: Female Wistar 9-10 months old rats were grouped (n=12/group) as - (1) Normal Control (NC), (2) Ovariectomized (OVX), (3) OVX+FG (hydroalcoholic seed extract of fenugreek), (4) OVX+C-DHA,(5) OVX+FG+C-DHA and (6) OVX+Estradiol. Groups 2- 6 were bilaterally OVX. FG, C-DHA was supplemented orally for 30 days, 14 days after ovariectomy. Assessment of learning and memory was performed by passive avoidance test. Oxidative stress and antioxidant markers were assessed by standard methods. Nissl stained hippocampal sections were analyzed to determine alterations in neural cell numbers in CA1, CA3 and dentate gyrus. Results: Supplementation of FG or/and choline with DHA to OVX rats, caused significant improvement in learning and memory as well as decreased neural cell deficits compared to the same in OVX rats. Further, significantly reduced levels of brain Malondialdehyde (MDA) and increased levels of Glutathione (GSH) were observed. Conclusion: Therapeutic supplementation of FG with choline-DHA significantly attenuates ovariectomy-induced neurocognitive deficits in rats.